Penyusunan Peta Digital Tematik Kependudukan Kalurahan Timbulharjo, Kapanewon Sewon, Kabupaten Bantul - Efendi, Hatta; Ragil, Candra; Nurkukuh, Dwi Kunto (Kurvamas, 2025)
Population data is one of the information needed for sustainable development planning. Timbulharjo Village, Sewon District, Bantul Regency has implemented a Population Administration Information System, and is currently initiating the creation of a digital population map to make it easier to create infographics, increasing community participation in the Village Development scheme. Community service activities in the form of compiling thematic digital population maps of Timbulharjo Village are carried out in three stages, namely (1) The preparation stage which contains activities for providing GPS and printed base maps, and downloading base map shapefile data, satellite imagery; (2) The implementation phase involves surveying village and hamlet boundaries using GPS and printed base maps, collecting population data from the Bantul Regency Population and Civil Registration Service, synchronizing population data in numbers with map locations, and editing digital maps using ArcGIS software, Google Earth, SAS Planet, and (3) The publication stage is carried out by publishing digital maps in Web-Map form, and publishing digital maps in print or poster form. The activity of compiling a thematic digital population map for Timbulharjo Village involved elements of the Village Government consisting of village officials and Hamlet Heads, student surveyors, and village assistants from the Ministry of Villages, Development of Disadvantaged Areas and Transmigration at the Bantul Regency level. The activity went smoothly with the longest stage being the agreement on boundaries between hamlets, while the boundaries between RT (Rukun Tetangga/ Neighborhood Association) had not yet been agreed because this boundary scheme had never been implemented in Timbulharjo District before.